2000
DOI: 10.1093/intimm/12.7.987
|View full text |Cite
|
Sign up to set email alerts
|

The interface between innate and acquired immunity: glycolipid antigen presentation by CD1d-expressing dendritic cells to NKT cells induces the differentiation of antigen-specific cytotoxic T lymphocytes

Abstract: In vivo administration of NKT cell ligand, alpha-galactosylceramide (alpha-GalCer), caused the activation of NKT cells to induce a strong NK activity and cytokine production by CD1d-restricted mechanisms. Surprisingly, we also found that alpha-GalCer induced the activation of immunoregulatory cells involved in acquired immunity. Specifically, in vivo administration of alpha-GalCer resulted in the induction of the early activation marker CD69 on CD4(+) T cells, CD8(+) T cells and B cells in addition to macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
158
4
6

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 204 publications
(179 citation statements)
references
References 32 publications
11
158
4
6
Order By: Relevance
“…This activity is thought to arise through iNKT cell-mediated activation of NK cells and rapid induction of IFN-␥ (43), with the antiangiogenic property of IFN-␥ playing a key role (44). It has been reported that some antitumor CTL activity may also be invoked through iNKT activation with ␣-GalCer (45,46). Our results would suggest that this activity would be dependent upon iNKT-mediated activation of DC that have acquired unique tumor Ags.…”
Section: Discussionmentioning
confidence: 52%
“…This activity is thought to arise through iNKT cell-mediated activation of NK cells and rapid induction of IFN-␥ (43), with the antiangiogenic property of IFN-␥ playing a key role (44). It has been reported that some antitumor CTL activity may also be invoked through iNKT activation with ␣-GalCer (45,46). Our results would suggest that this activity would be dependent upon iNKT-mediated activation of DC that have acquired unique tumor Ags.…”
Section: Discussionmentioning
confidence: 52%
“…41,45,49,54 -56,58,61 By responding to infectious or other challenges prior to conventional adaptive T cells, CD1d-reactive T cells could have the potential to influence the course of local and systemic bias of immune responses. Activated CD1d-reactive T cells can stimulate NK cells 59 and cytotoxic T lymphocytes, 23,24,62 actions dependent in part on the ability of the CD1d-reactive T cells to produce IFN-␥. In addition to the possible role of CD1d-reactive T-cell-produced cytokines as facilitators of immune responses, IFN-␥ and other cytokines may play a role in the clearance of pathogens, especially viral pathogens.…”
Section: Roles Of Cd1d-reactive Nkt Cellsmentioning
confidence: 99%
“…Data from many groups indicate that iNKT functions can be mediated through interactions with CD1d ϩ APC including DCs and B cells (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Murine studies have shown that iNKT activation can be enhanced by B7 ligation of CD28 and that IL-12 produced by DCs can further enhance iNKT IFN␥ production (11,12,20).…”
mentioning
confidence: 99%